PROFIL PEREMPUAN PEKERJA TAMBANG MANGAN Kasus : Tambang Rakyat Kamang Saiyo Nagari Kamang Kecamatan Kamang Baru Kabupaten Sijunjung - PUTRI TAMA, ENGLA DARUL (Pendidikan Sosiologi, 2014)
This research was background by decreasing citizen income Nagari kamang and next society starts to come to mining mangan. So that citizen income which is low can increase. In mangan mining Kamang Saiyo which is located in Nagari Kamang Kecamatan Kamang Baru Kabupaten Sijunjung, most of workers are housewife; meanwhile working in mine is not easy. The purpose of this research is to describe profile of womanâs mine mangan and the reasons why they choose work in mangan mining Kamang Saiyo which is located in Nagari Kamang Kecamatan Kamang Baru Kabupaten Sijunjung. The theory which is used is Phenomenology theory according to Alfred Schlutz. The research method which is used in this research is quality enclose by descriptive research to describe the problem. The informant taken is used by purposive sampling by 8 informants. The data type of this research is prime data. This data is collected by using observation technique, interview and documentation, and also using tools like interview guide, book, pen, and hand phone. After the data is gotten, itâs analyzed by data reduction, data display, and data verification (conclusion) The result of this result 0stated that 1. Profile of the woman who works in mangan mine are above 25 years old and last education is elementary school, with burden for family and income 600 hundred thousands rupiahs per month and also to increase the lack of income, half of woman have land and goods like garden and shop. 2. The reason of woman to choose work in mine are: a) to complete family need, b) that job doesnât need special skill. Power was enough, c) do that mining job because takes the advantage of working land.